Un modelo univariante para la predicción de crisis empresariales en un contexto macroeconómico turbulento - Terreno, Dante Domingo (2022)
The aim this study is evaluate the usefulness of relation between future cash flows with liability, it´s identified how ratio ability to paid debts, to forecast the financial crises. The analysis is made for companies of Argentina Capital Market, that it faces a context with a strong macroeconomic imbalance. The conclusion what arrives in this study point out that ability to paid debts measure core operating income shows most accuracy that ability to paid debts for the EBITDA, net income, operating flows cash and the Z-score Altman (1968). Moreover, the companies with a higher leverage and less profitability have a higher possibility of get in financial crisis, and it´s found that main cause of financial crisis is the drop of operating incomes.